2014
DOI: 10.1111/jvim.12370
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Diagnostic and Treatment Modalities for Intracranial Tumors

Abstract: Intracranial neoplasia is a common clinical condition in domestic companion animals, particularly in dogs. Application of advances in standard diagnostic and therapeutic modalities together with a broad interest in the development of novel translational therapeutic strategies in dogs has resulted in clinically relevant improvements in outcome for many canine patients. This review highlights the status of current diagnostic and therapeutic approaches to intracranial neoplasia and areas of novel treatment curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
121
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(129 citation statements)
references
References 206 publications
(402 reference statements)
3
121
0
5
Order By: Relevance
“…Our efforts include the identification of pharmacologically tractable molecular targets common to human and canine brain tumors, as well as the development of novel macroscopic methods of CNS drug delivery that overcome the limitations imposed by the bloodbrain barrier (BBB) and blood brain tumor barrier (BBTB) (13,14). The design and conduct of clinical trials in dogs with naturally occurring brain tumors is a major mechanism by which we assess our drug and device discoveries (10,13).…”
Section: Preclinical Testing Of Various Therapeutic Methods (Convectimentioning
confidence: 99%
See 1 more Smart Citation
“…Our efforts include the identification of pharmacologically tractable molecular targets common to human and canine brain tumors, as well as the development of novel macroscopic methods of CNS drug delivery that overcome the limitations imposed by the bloodbrain barrier (BBB) and blood brain tumor barrier (BBTB) (13,14). The design and conduct of clinical trials in dogs with naturally occurring brain tumors is a major mechanism by which we assess our drug and device discoveries (10,13).…”
Section: Preclinical Testing Of Various Therapeutic Methods (Convectimentioning
confidence: 99%
“…It has been suggested that inclusion of preclinical canine studies in the drug development pathway could result in billions of dollars of research savings, principally by improving the design of Phase II human clinical trials and thus potential avoidance of the historically high latestage failure and attrition rates of new cancer agents (9,11). Dogs with spontaneous brain tumors have been assimilated into several comparative neuro-oncology research programs in an effort to accelerate the development and translation of cancer drugs to the clinic, and to mutually improve the lives of dogs and humans with brain tumors (5,10,(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…14 Brachycephalic (“smushed face”) breeds, particularly Boxers and Boston Terriers, are overrepresented in glioma diagnoses, which account for a third or more of all primary intra-axial (inside the brain tissue) brain tumors in dogs. 1517 Dolicocephalic (long-nose) breeds, such as Golden Retrievers and German Shepherds, more often develop meningiomas, the most frequently reported primary extra-axial (outside the brain tissue) brain tumor in dogs. 18 Together, gliomas and meningiomas account for about 80% to 90% of canine primary brain tumors, 15 and these are two of the most common brain tumors to develop in humans as well.…”
Section: Brain Tumor Surrogatesmentioning
confidence: 99%
“…1517 Dolicocephalic (long-nose) breeds, such as Golden Retrievers and German Shepherds, more often develop meningiomas, the most frequently reported primary extra-axial (outside the brain tissue) brain tumor in dogs. 18 Together, gliomas and meningiomas account for about 80% to 90% of canine primary brain tumors, 15 and these are two of the most common brain tumors to develop in humans as well. 19 Similar to human patients, the prognosis for dogs with brain tumors is poor with a median survival of 65 days (4 studies, 138 dogs) with symptomatic therapy only, 312 days (6 studies, 108 dogs) with surgical treatment, and 351 (13 studies, 428 dogs) with radiation therapy.…”
Section: Brain Tumor Surrogatesmentioning
confidence: 99%
“…Primary brain tumours occur more commonly in dogs than any other domestic species [1] and while their incidence is only reported to range from 14-20/100,000 to up to 3% of the canine population, [2,3] the effects of brain tumours on both dogs and their families are often devastating. Meningiomas, the most common primary brain tumour of dogs [4,5] have shown good response to more extensive surgical resection [6][7][8] and both conventional and stereotactic radiation therapy [9,10].…”
Section: Introductionmentioning
confidence: 99%